THERMAL DECOMPOSITION KINETICS OF LANTHANUM OXALATE HYDRATE PRODUCT TREATMENT FROM MONAZITE - M V Purwani; Suyanti Suyanti; Wisnu Ari Adi (Jurnal Sains Materi Indonesia, 2019)
THERMAL DECOMPOSITION KINETICS OF LANTHANUM OXALATE HYDRATE PRODUCT TREATMENT FROM MONAZITE. Unreacted shrinking core model variation was developed for calcination and solid thermal decomposition reaction to non catalytic gas and no gas reactants were involved. In this research, thermal decomposition of lanthanum oxalate hydrate product treatment of monazite. The parameters for modeling are the time and temperature of thermal decomposition. The time was between 0 - 150 minutes with 30 minute intervals and the temperature range between 600 – 700 oC with 100 oC intervals. Based on the experimental data it can be concluded that the most suitable model was unreacted core sphere ash diffusion controls and obtained the relation between temperature T oC with diffusion coefficient D following equation D = 0.0011 T + 0.5175 with linearity R² = 0.9561. Another possible model was the sphere reaction control and obtained the relationship between 1 / T (K) and reaction rate constant ks was ks = 48873.e -4.88 / RT with activation energy = 4.88 kJ. The relationship between time t with rc (radius of particles at time t) at various temperatures and the relation between temperature and rc at various times follows the exponential line equation. If temperature and time parameters were combined will find the relation between time and temperature with rc following the equation ln rc = -0.9536 (9E-04 T + 0.005 T) + 4.9976.